Effects of supplemental phytase on nutrient digestibility and performance of sows fed diets with high or low native phytase activity - E.R. Grela; J. Matras; A. Czech (Czech Journal of Animal Science, 2011)
Two experiments were conducted to examine the influence of addition of microbial phytase to diets differing in native phytase content, on the performance of sows and digestibility of nutrients. Barley and wheat grains relatively poor in native phytase used in Experiment 1 mixtures were replaced by triticale and rye (rich in this enzyme) in Experiment 2 diets. There were 3 groups in each experiment. Group I (control) received basal diets enriched with dicalcium phosphate (10 g/kg), group II (negative control) was fed basal diets without any additive, and group III (negative control) was supplemented with microbial phytase (500 PU/kg). Body weights of sows were monitored at mating, before parturition, immediately after parturition and at weaning. Apparent ileal and total tract digestibility of basal nutrients, detergent fibre fractions, Ca and P of the investigated diets from particular treatments was determined. Microbial phytase (Natuphos®, BASF AG, Ludwigshaven, Germany) supplemented at 500 PU/kg in pregnancy and lactation diets based on barley and wheat resulted in smaller body weight losses during lactation and higher weight gain over the whole cycle. Synergistic effects of microbial phytase and native phytase on body weight changes of sows, feed conversion ratio during pregnancy, and apparent (ileal and total tract) digestibility of both organic matter and minerals (total and phytic phosphorus and calcium) were found out.